Geochemical investigation of tar balls collected on a beach on Žirje island (Croatia) using petroleum biomarkers - Marinović, Slavica, inženjerka kemije (Array, 2021)
Tar balls are frequently reported as indicators of the extent of marine pollution owing to spill incidents of crude oil or petroleum products. Representative tar ball samples collected on a beach on Žirje Island, Croatia, were geochemically characterised by gas chromatography coupled to mass spectrometry (GC/MS) in order to identify correlations between them and investigate potential sources. The chemical analysis of petroleum biomarkers, hopanes, and steranes, detected by gas chromatography/mass spectrometry (GC/MS) generates information of great importance to environmental forensic investigations in terms of determining the source of spilled oil, differentiating and correlating oils, and monitoring the degradation process and weathering state of oils under a wide variety of conditions. The chromatographic signatures of hopane and sterane biomarkers in tar ball samples from Žirje Island were compared. Characteristic hopane and sterane fingerprints show that all the tar ball samples originated from crude oil spills. This study indicates that, the major source of tar balls was likely to be the same type of crude oil as evident from the petroleum biomarker fingerprints.